W stronę zintegrowanych badań regionalistycznych. Kilka refleksji na marginesie konferencji "Ziemia Lubuska jako przedmiot badań" (Zielona Góra, 24-25 maja 2023) = Towards integrated regionalist research: reflections on the conference "Ziemia Lubuska jako przedmiot badań" [Lubuskie Region as an object of research] (Zielona Gora, 24-25 may 2023) - Mikołajczak, Małgorzata (1966- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper builds on the concept of integrated regionalist research, a framework that emerged alongside the rise of regionalism as a social movement and was first articulated in Poland through Stefan Żeromski`s play "Uciekła mi przepioreczka" [My Little Quail Has Flown]. In the context of contemporary developments in the humanities and social sciences, this concept is revisited and reaffirmed as a valuable research approach. Its relevance was underscored during the inaugural conference in the series Region w dialogu. "Zintegrowane badania nad Ziemią Lubuską" [Region in Dialogue: Integrated Research on the Lubuskie Region], held in Zielona Gora on 24-25 May 2023, under the theme "Ziemia Lubuska jako przedmiot badań" [The Lubuskie Region as an Object of Research].
Keywords: Ziemia Lubuska; regionalizm; tradycja badawcza; zintegrowane badania regionalistyczne; Lubuskie Region; regionalism; research tradition; integrated regionalist research